1992
DOI: 10.1037/0882-7974.7.4.518
|View full text |Cite
|
Sign up to set email alerts
|

Aging persons' estimates of vehicular motion.

Abstract: Estimated arrival times of moving autos were examined in relation to viewer age, gender, motion trajectory, and velocity. Direct push-button judgments were compared with verbal estimates derived from velocity and distance, which were based on assumptions that perceivers compute arrival time from perceived distance and velocity. Experiment 1 showed that direct estimates of younger Ss were most accurate. Older women made the shortest (highly cautious) estimates of when cars would arrive. Verbal estimates were mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
55
2

Year Published

1998
1998
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(68 citation statements)
references
References 15 publications
11
55
2
Order By: Relevance
“…Overall, the results demonstrated very few differences with respect to age, apart from the stronger reliance on heuristic cues by the older group in the audio-visual condition. These results are somewhat inconsistent with other studies of visual TTC, which have demonstrated more conservative estimates (i.e., underestimations of TTC) by older adults (e.g., DeLucia et al, 2003;Hancock & Manser, 1997;Schiff et al, 1992).…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Overall, the results demonstrated very few differences with respect to age, apart from the stronger reliance on heuristic cues by the older group in the audio-visual condition. These results are somewhat inconsistent with other studies of visual TTC, which have demonstrated more conservative estimates (i.e., underestimations of TTC) by older adults (e.g., DeLucia et al, 2003;Hancock & Manser, 1997;Schiff et al, 1992).…”
Section: Discussioncontrasting
confidence: 56%
“…Healthy older adults often experience agerelated sensory, cognitive, and motor declines that may affect TTC estimates and may result in relative weightings of visual and auditory sensory inputs that differ from the relative weightings in younger adults. Indeed, differences in visual TTC judgments have been previously observed between younger and older adults (e.g., DeLucia, Bleckley, Meyer, & Bush, 2003;Hancock & Manser, 1997;Schiff, Oldak, & Shah, 1992). However, age differences have not been considered in TTC judgments when auditory or concurrent visual and auditory information is presented.…”
mentioning
confidence: 99%
“…5 Consistent with the pattern of results reported in previous studies, estimated TIC increased as actual TIC increased, and judgment accuracy decreased with larger TTCs and consisted primarily of underestimations. The mean percentage accuracy (judged TIC * 100/actual Trc; Schiff & Oldak, 1990;Schiff et al, 1992) was significantly greater with lateral motion than with approach motion with the near distance and with the far distance when TIC was 0.75 s. In addition, the percentage accuracy was greater with 4We used the same apparatus as in Experiment 1. Results of an experiment with modifications of a subset of scenes in the control study suggested that the degree of simulated computer aliasing (see Watt, 1989) or irregularity in an object's optical expansion (which varies with display resolution) does not affect time-to-contact estimates (see also DeLucia, 1991).…”
Section: Resultsmentioning
confidence: 93%
“…Also, when 8 different observers were instructed explicitly to mentally extrapolate or continue the object's motion in their mind after it disappeared, a comparison of the results with those of the control study indicated no effect of instructions. (Schiff et al, 1992); the means indicated underestimations of TrC in near-distance scenes. The latter findings are consistent with results of Experiment 1, in which near scenes were relatively more biased toward overshoots.…”
Section: Resultsmentioning
confidence: 99%
“…In TTA block, raw estimates of TTA were transformed into a TTA estimate ratio, which was the proportion of estimated TTA relative to the actual TTA (e.g. Schiff, Oldak, & Shah, 1992) prior to the statistical analysis. A value above 1 indicates an overestimation of TTA, a value below 1 indicates an underestimation.…”
Section: Discussionmentioning
confidence: 99%